Physical exercise-related manifestations of long COVID: A systematic review and meta-analysis - Chen Zheng; Jun-Jie Chen; Zi-Han Dai; Ke-Wen Wan; Feng-Hua Sun; Jun-Hao Huang; Xiang-Ke Chen (Elsevier, 2024)
Objective: This study aims to systematically assess physical exercise-related symptoms of post-acute sequelae of SARS-CoV-2 infection (PASC or long COVID) in coronavirus disease 2019 (COVID-19) survivors. Methods: Eight databases were systematically searched on March 03, 2024. Original studies that compared physical exercise-related parameters measured by exercise testing between COVID-19 survivors who recovered from SARS-CoV-2 infection over 3 months and non-COVID-19 controls were included. A random-effects model was utilized to determine the mean differences (MDs) or standardized MDs in the meta-analysis. Results: A total of 40 studies with 6241 COVID-19 survivors were included. The 6-min walk test, maximal oxygen consumption (VO2max), and anaerobic threshold were impaired in COVID-19 survivors 3 months post-infection compared with non-COVID-19 controls in exercise testing, while VO2 were comparable between the two groups at rest. In contrast, no differences were observed in SpO2, heart rate, blood pressure, fatigue, and dyspnea between COVID-19 survivors and non-COVID-19 controls in exercise testing. Conclusion: The findings suggest an underestimation of the manifestations of PASC. COVID-19 survivors also harbor physical exercise-related symptoms of PASC that can be determined by the exercise testing and are distinct from those observed at rest. Exercise testing should be included while evaluating the symptoms of PASC in COVID-19 survivors.